Evolvable Assembly Systems: A Distributed Architecture for Intelligent Manufacturing. Issue 3 (2015) - Chaplin, J.C.; Bakker, O.J.; de Silva, L.; Sanderson, D.; Kelly, E.; Logan, B.; Ratchev, S.M.
Abstract: Modern manufacturing companies are under economic pressure to respond more rapidly to a changing production environment, including short product life cycles, individually customisable products, and the introduction of new disruptive manufacturing processes. This paper details a new manufacturing philosophy and software architecture for Evolvable Assembly Systems, based on the principles of decentralization, context-awareness and intelligent resources, that is implemented using intelligent agent technology and a data distribution service. We also detail the Smart Manufacturing and Reconfigurable Technology demonstrator - an instantiation of the Evolvable Assembly Systems architecture - that implements a proof-of-concept abstract custom pharmaceuticals production line.